Facile and Efficient Route to the Synthesis of Ethyl 3-Oxo-Cyclohexene- 1-Carboxylate as a Valuable Synthetic Intermediate - Mamaghani, M.; Jafarian, M. (Asian Journal of Chemistry, 2010)
Cyclohexanol-1-ethylcarboxylate was prepared from readily available cyclohexanone cyanohydrin in 85.5% and treated with thionyl chloride (SOCl2) in the presence of pyridine under argon atmosphere to provide ethyl cyclohexene-1-carboxylate in 80% yield. This product was conveniently transformed to ethyl 3-oxo-cyclohexene-1-carboxylate in a moderate yield (52%).